LIPID TETRAD INDEX IN CORONARY ARTERY DISEASE: A CROSS-SECTIONAL STUDY IN INDIAN POPULATION - Dr Mrityunjay Kumar; Dr Pallavi Ranjan Anand (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
IntroductionCoronary artery disease (CAD) is a leading cause of morbidity and mortality worldwide, with India bearing a significant burden. Dyslipidemia, characterized by elevated triglycerides (TG), low high-density lipoprotein cholesterol (HDL-C), and high low-density lipoprotein cholesterol (LDL-C), is a major risk factor for CAD. Traditional lipid profiles have limitations in predicting cardiovascular risk. Recently, the lipid tetrad index (LTI), calculated as [(TG × LDL-C) / (HDL-C)²], has emerged as a promising marker. This study aimed to assess the LTI in subjects with CAD and compare it with healthy controls in an Indian population.Materials and MethodsThis cross-sectional study was conducted at a tertiary care hospital in India. We enrolled 200 consecutive patients with CAD (confirmed by angiography) and 200 age- and sex-matched healthy controls. Exclusion criteria included patients with acute coronary syndrome, severe liver or kidney disease, and those on lipid-lowering therapy. Fasting blood samples were collected, and lipid profiles were analyzed using standard methods. LTI was calculated using the formula: LTI = [(Total Cholesterol x Triglycerides x Lipoprotein a) / (HDL-C)]]. Data were analyzed using SPSS version 22.ResultsIn this cross-sectional study of 200 CAD patients and 200 healthy controls, Lipid Tetrad Index (LTI) was significantly higher in CAD patients (p < 0.001). LTI correlated positively with total cholesterol, triglycerides, and lipoprotein(a) and negatively with HDL-cholesterol. Receiver operating characteristic curve analysis revealed LTI's good discriminatory power for CAD (AUC = 0.829, 95% CI: 0.783-0.875). These findings suggest LTI as a valuable marker for cardiovascular risk assessment.ConclusionThe lipid tetrad index is a valuable marker for predicting cardiovascular risk in Indian patients with coronary artery disease. Its calculation is simple and can be easily incorporated into routine lipid profiling. Further studies are needed to validate LTI as a predictive tool for CAD in larger Indian populations.